Study of metalloproteinases in the blood of goats experimentally infected with caprine encephalitis arthritis virus - Galiza, Ylana Santos de; Eloy, Angela Maria Xavier; Pinheiro, Raymundo Rizaldo; Peixoto, Renato Mesquita; Lima, Ana Milena César; Barroso, Maria Luane da Silva; Fonseca, Luzianna Macedo (Semina: Ciências Agrárias, 2020)
Caprine arthritis encephalitis is a lentiviral disease that leads to considerable losses in goat farming. In the acute phase of viral infection, though antiviral antibodies are produced by the host's immune system, they are not sufficient to be detected by serological tests. Acute infections begin with an incubation period, during which the viral genome replicates and host innate responses are initiated. Matrix metalloproteinases (MMPs) are enzymes that play an important role in the physiological and pathological processes of tissue remodeling. The present study aimed to evaluate the expression of MMPs and their activity in the blood serum of goats experimentally infected with caprine arthritis encephalitis virus (CAEV). Five dairy goats, aged 3-4 years, were intravenously inoculated with CAEV Cork strain (titer: 105-6 TCID50/mL) after being tested negative for CAEV thrice at consecutive intervals of 30 days using western blot analysis and nested-PCR. The study included three stages: S1 or pre-infection stage; S2 or seroconversion stage, corresponding to the occurrence of first seroconversion; and S3 or post-seroconversion stage, corresponding to 23 weeks after seroconversion. Zymography was performed for the samples using gelatin zymography gels (12.5%), which were subjected to electrophoresis at 170V, 1A, and 300W for 50-70 min. The density of MMP-2 was found to be lower at S1 (1456.20 pixels) than that at S2 and S3 (1943.80 and 2104.40 pixels, respectively) (P < 0.05); and the density of MMP-9 was found to be lower at S3 (133.60 pixels) than that at S1 and S2 (359.60 and 370.60 pixels, respectively). The density of proMMP-2 was low at S1 and S3 (130.45 and 145.20 pixels, respectively). On the other hand, the density of proMMP-9 was statistically different between S1 and S3 (89.22 vs. 415.60 pixels). Both proMMP-2 and proMMP-9 were absent at S2. Thus, MMP-2 and MMP-9 exhibited opposite behaviors depending on the stage of infection. As the greatest activity of MMP-2 was detected at stage S3, we suggest that MMP-2 can be used as a biomarker for complementary diagnosis of acute CAEV infection. In addition, the presence of proMMP-13 can be used to indicate active viral infection.